WELL LEG COMPARTMENT SYNDROME: THE DEBIT SIDE OF HEMILITHOTOMY POSITION - Noordin, Shahryar; Allana, Salim; Wajid, MA (Journal of Ayub Medical College Abbottabad, 2009)
We describe a case of well leg compartment syndrome following unilateral lithotomy position in a patient undergoing contralateral antegrade intramedullary femoral nailing. Following two-incision four compartment fasciotomy, the patient recovered with no residual defects. We dissuade use of the hemilithotomy position for antegrade femoral nailing procedures in favour of another previously described position, because this predisposes patients to position-associated complications without offering any substantial advantage. Keywords: Compartment syndrome, well-leg, hemilithotomy